Politics at the Local–Global Intersection: Meanings of Bentuhua and Transnational Feminism in China. Issue 1 (2nd January 2016) - Wesoky, Sharon R.
Abstract: This article examines contemporary Chinese feminism's processes of "connecting with the international tracks" as well as bentuhua (indigenisation), arguing that these processes are inseparable from both domestic and international power relations and thus asserting the need for a critical perspective on bentuhua . An "institutional-discursive" focus on both political and cultural contexts reveals that the usage of bentuhua can be literally and metaphorically spatial in quality, as well as regarded as a resource that is part of the grammar of social transformation in China. Neoliberal globalisation promotes a "project"-oriented approach to feminist activism that has benefits and costs. Transnationalism can be a source of resistance to the continued authoritarian party-state, as well as to homogenising effects of nationalist tendencies. Thus, from a theoretical standpoint it is useful to comprehend contemporary Chinese feminist thought from the understanding that the local and the global are inextricably interconnected.